Heat acclimation and thirst in rats. Issue 12 (23rd December 2015) - Barney, Christopher C.; Schanhals, Elizabeth M.; Grobe, Justin L.; Andresen, Bradley T.; Traver, Michael
Abstract: The effects of heat acclimation on water intake and urine output responses to thermal dehydration and other thirst stimuli were studied in male Sprague–Dawley rats. Rats were heat acclimated by continuous exposure to a 34°C environment for at least 6 weeks. Thermal dehydration‐induced thirst was brought about by exposing the heat‐acclimated rats and control rats housed at 24°C to a 37.5°C environment for 4 h without access to food or water. Heat acclimation reduced evaporative and urinary water losses and the increases in plasma sodium and osmolality during thermal dehydration, which led to a reduction in thermal dehydration‐induced thirst. Heat acclimation reduced the rate of rehydration following thermal dehydration but did not alter the final rehydration level, indicating that heat acclimation does not alter the primary control of thermal dehydration‐induced thirst. Heat acclimation did not alter water intake or urine output following administration of hypertonic saline, which selectively stimulates intracellular thirst, but led to greater water intake following administration of angiotensin II, which plays an important role in extracellular/volemic thirst, and following water deprivation, which activates both thirst pathways. Cardiovascular responses to angiotensin II were not altered by heat acclimation. Heat acclimation thus reduces water loss during heat exposure in rats, but does not have major effects on thermal dehydration‐induced or extracellular thirst but does appear to alter volemic thirst. Abstract : Heat acclimation did not alter the ability of rats to rehydrate following thermal dehydration but did reduce the level of evaporative water loss and the rate at which thermal dehydration developed. Heat acclimation of rats enhanced the water intake response to angiotensin II, a hormone that plays an important role in volemic thirst, without altering the water intake responses to increases in plasma osmolality/sodium concentration induced by administration of hypertonic saline. Heat acclimation also increased water intake and improved hydration after 24 h of water deprivation.